Comparative clinical efficacy of acupuncture-related therapies for ulcerative colitis: a systematic review and network meta-analysis - Zhang, Longtao; Sun, Yanxiao; Ru, Ziyang; Li, Dan; Ma, Yuxia (Frontiers in Medicine, 2025)
BackgroundUlcerative colitis (UC) is a chronic and recurrent inflammatory bowel disease. Current drug treatments are often associated with side effects, unstable efficacy, and high relapse rates. Therefore, exploring complementary and alternative therapies such as acupuncture is of significant importance for optimizing UC clinical management strategies. This study employs a network meta-analysis method to systematically compare the efficacy and safety of various acupuncture-related therapies in treating UC, aiming to provide evidence-based guidance for selecting the optimal clinical intervention.MethodsWe systematically searched 8 databases for randomized controlled trials (RCTs) of acupuncture-related therapies for ulcerative colitis, including China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP Database, China Biological Medicine (CBM), PubMed, EMbase, the Cochrane Library, and Web of Science. The total effective rate, Mayo score, Baron endoscopic score were used for primary outcomes, interleukin-6 (IL-6) levels, tumor necrosis factor-alpha (TNF-α) levels, and relapse rate were selected as secondary outcomes. The Cochrane risk of bias tool (RoB 2.0) was used to assess the quality of the articles, and StataMP 18 was used for statistical analysis. Heterogeneity and consistency were assessed, and the comparative effectiveness of different acupuncture interventions was ranked using Surface under the cumulative ranking curve (SUCRA).ResultsA total of 76 RCTs were included, involving 7,484 participants. Auricular acupressure combined with Chinese herbal medicine (AA + CHM) (RR 1.71, 95% CI: 1.47, 1.99, SUCRA = 99.9%) was shown to have effective to improving total effective rate. For Mayo score, the most effective intervention was acupuncture combination therapy (ACU-CT) (SMD –4.85, 95% CI: –6.66, –3.05, SUCRA = 97.5%). In terms of reducing Baron endoscopic score, ACU-CT (SMD-2.31, 95% CI: –3.81, –0.81, SUCRA = 84.1%) had the best efficacy. For IL-6 levels, warm acupuncture (WA) (SMD –3.10, 95% CI: –4.56, –1.65, SUCRA = 96.1%) showed the best efficacy. For TNF-α levels, warm acupuncture combination therapy (WA-CT) (SMD –2.32, 95% CI: –4.54, –0.10, SUCRA = 76.8%) demonstrated the best efficacy. For recurrence rate, Acupuncture (ACU) (OR 0.15, 95% CI: 0.03, 0.65, SUCRA = 89.3%) achieved the greatest reductions. SUCRA analysis showed that WA, ACU-CT, WA-CT, and acupoint catgut embedding (ACE) ranked highest in most of the outcomes. Acupoint frequency statistics revealed that the most commonly used acupoints for treating UC were Tianshu (ST25), Zusanli (ST36), Shangjuxu (ST37), Zhongwan (CV12), Guanyuan (CV4), Dachangshu (BL25), Pishu (BL20), Shenque (CV8), Qihai (CV6), and Sanyinjiao (SP6).ConclusionThese findings may provide preliminary evidence-based guidance for acupuncture-related interventions as a potential complementary or alternative treatment for patients with UC, particularly those who have poor responses to conventional pharmaceutical treatment. In the future, more large-sample, high-quality RCTs are needed to further confirm the long-term efficacy and mechanisms of different acupuncture interventions.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251082924.